Hostile take-overs: A review of defensive techniques currently used by target companies - N. Bhana (South African Journal of Business Management, 1984)
Take-overs of companies are being increasingly used as a means of business growth. Take-over candidates are decreasing and acquiring companies are becoming more aggressive in pursuing take-overs. The target companies have retaliated by using several new techniques to avoid hostile take-overs. Anti-take-over amendments to the company's Memorandum and Articles of association, 'golden parachute' arrangements, and the simultaneous bid for the acquiring company are being extensively used to defend hostile take-overs. The controversial nature of these new strategies has provoked heated academic debate as well as emotional arguments between business managers and shareholders. The high cost of implementing the new strategies to defend take-overs has generated much adverse publicity in the United States. By contrast these new techniques have not found widespread use in South Africa. It can be expected that at some stage in the future these techniques will be implemented by the target companies in South Africa. The public policy implications of using these techniques are discussed in this article. The need to provide guide-lines on the use of new strategies to defend hostile take-overs is recommended. The listed companies in South Africa are instrumental in undertaking major take-overs resulting in increased business concentration. It is recommended that the Johannesburg Stock Exchange should provide guidelines on acceptable methods to defend hostile take-overs.
Keywords: 650